Pengaruh Leverage, Likuiditas, dan Saham Publik terhadap Luas Pengungkapan Sukarela dalam Laporan Tahunan - Mujiyono Mujiyono; Magdalena Nany (Jurnal Akuntansi dan Bisnis, 2006)
Company’s annual report is one of the information that connecting the company’s management and their stockholders. The study about voluntary disclosure in an annual report will provide some insight about disclosure practices in Indonesian firms. The objective of this research was to give empirical evidence about the effects of leverage, liquidity, and firm public own proportion on voluntary disclosure both partially and simultaneously. Seventy four companies were analyzed by multiple regression analysis. The results show that leverage insignificantly has positive effect on voluntary disclosure. Liquidity also insignificantly has positive effect on voluntary disclosure. But firm public own proportion insignificantly has negative effect on voluntary disclosure. The result also show that leverage, liquidity, and firm public own proportion simultaneously have insignificant effect on voluntary disclosure .